Development of a body fluid identification multiplex via DNA methylation analysis. Issue 18 (18th July 2019) - Gauthier, Quentin T.; Cho, Sohee; Carmel, Justin H.; McCord, Bruce R.
Abstract: The goal of this study is to develop an epigenetic multiplex for body fluid identification based on tissue specific DNA methylation. A series of genetic loci capable of discerning the origin of DNA as coming from saliva, blood, vaginal epithelia, or semen were used for this application. The markers – BCAS4, CG06379435, VE_8, and ZC3H12D – were amplified together and then sequenced via pyrosequencing. Methylation values for cytosine guanine dinucleotide (CpG) sites at each locus were then measured across the four markers. In total, 124 samples were collected, and bisulfite modified to convert unmethylated DNA to uracil. This converted DNA was then amplified via multiplex PCR with reverse primers containing a biotin molecule. Biotinylated PCR products were then analyzed using pyrosequencing to generate a series of pyrograms containing 18 CpG sites. The percent methylation at each CpG site was determined, and then agglomerative hierarchical cluster analysis was used to create a model to indicate sample origin. Further analysis reduced the number of CpG sites required for optimal determination of body fluid type to five. This study demonstrates an efficient multiplexed body fluid identification process utilizing DNA methylation that can be easily implemented in forensic laboratories.